2022
DOI: 10.3389/fpubh.2021.719485
|View full text |Cite
|
Sign up to set email alerts
|

Hunger and Adherence to Antiretroviral Therapy: Learning From HIV Positive Caregivers of Orphans and Vulnerable Children in Tanzania

Abstract: The association between hunger and adherence to antiretroviral therapy (ART) is less known especially in vulnerable populations receiving HIV care and treatment services. Caregivers of orphans and vulnerable children (OVC) are vulnerable and likely to experience hunger due to additional economic pressure in caring for OVC. Using data from the community–based, USAID–funded Kizazi Kipya project, this study assesses the association between hunger and ART adherence among caregivers of OVC in Tanzania. HIV positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…This nding revealed that patients who have no caregiver had higher hazards of death as compared with their counterparts. This nding is in line with any other studies (11,40,41), patient with HIV on ART needs intensive care and support from their families, relatives, neighbors, and others like health care providers for improving their level of adherence to retain the care. This support may in different perspectives like social, economic ( nancially) and psychological as well as (11,35) the belongingness of this support makes the patient being hopeful and can disclose their HIV status to others, this disclosure helps them to collect their medication on time, minimize the level of stigmatization at the workplace and within the community (42).…”
Section: Discussionsupporting
confidence: 89%
“…This nding revealed that patients who have no caregiver had higher hazards of death as compared with their counterparts. This nding is in line with any other studies (11,40,41), patient with HIV on ART needs intensive care and support from their families, relatives, neighbors, and others like health care providers for improving their level of adherence to retain the care. This support may in different perspectives like social, economic ( nancially) and psychological as well as (11,35) the belongingness of this support makes the patient being hopeful and can disclose their HIV status to others, this disclosure helps them to collect their medication on time, minimize the level of stigmatization at the workplace and within the community (42).…”
Section: Discussionsupporting
confidence: 89%
“…Research shows that children living with HIV/AIDS in Tanzania struggle to adhere to antiretroviral therapy [5][6][7] compounded by various socio-economic factors affecting the routine administration of medicines at home.…”
Section: Introductionmentioning
confidence: 99%